Developing community technology: A profile website for SDI Miftahus Sholihin - Hendro Priyatman; Seno Darmawan Panjaitan; Hilda Hilda; Eka Kusumawardhani; Leonardus Sandy Ade Putra (University of Merdeka Malang, 2024)
The Community Service Program titled